Correlation Between Adolescent Pregnancy With Labor Complication in Puskesmas Galis Bangkalan Regency - Sherina Pradita Eka Wahyudi; Rize Budi Amalia; Endyka Erye Frety (Journal of Midwifery, 2023)
Adolescent pregnancy is a major health issue, leading to an increase in maternal and infant mortality due to complications in delivery. The purpose of this study was to analyze the correlation between adolescent pregnancy and delivery complications at the Puskesmas Galis, Bangkalan Regency. This research method was quantitative observational with a case control design. The population of mothers who gave birth in the working area of Puskesmas Galis, Bangkalan Regency in January - December 2022. The study used samples of 20 adolescent pregnancies with the number of controls was adjusting the amount of samples as many as 20. Case sampling was carried out by consecutive sampling with inclusion criteria for giving birth aged â‰¤ 35 years, primiparous, and exclusion criteria for incomplete medical record data, multiple pregnancies, pregnancies with heart disease, pregnancies with respiratory tract diseases, pregnancies with kidney disease, pregnancies with diabetes mellitus, pregnancies with tumors. Adolescent mothers were more likely to have preterm labor (20%), premature rupture of membranes (20%), prolonged labor with stage 1 abnormalities (5%), CPD (5%), and SC delivery methods (5%), and have a higher risk of labor complications (45%) (P-value 0.034, OR 7.364, 95% CI: 1.337 â€“ 40,548). Adolescent age increases the risk of labor complications